SEGO BORANAN IN BUYING AND SELLING CONTEXT OF MATHEMATICS PROBLEM SOLVING - Ardiansyah, Adi Satrio; Fitriana, Dea Rizqi; Chafshoh, Nabillah Arifa; Isbianto, Isbianto; Ali, Mat; Susnasuhah, Lilik (Ethnomath Association in cooperation with Universitas Negeri Yogyakarta, 2024)
This study aims to develop problem based learning in ethnomathematics-based textbooks through Sego Boranan's buying and selling activities to improve students' problem-solving abilities in social arithmetic material. Research & development were carried out a procedure of 3D (Define, Design, & Develop). The feasibility assessment was carried out by experts and practitioners using the feasibility sheet, the readability assessment by students who had obtained Social Arithmetic material using readability sheets, and student responses by students who were studying Social Arithmetic material using a student response questionnaire. The textbooks developed were included in the very feasible criteria, was easy to understand, and very feasible to be implemented in learning mathematics. Although it is suggested that using an experimental method can test the effectiveness of using this textbook on learning outcomes and students' problem-solving abilities, this paper presented examples of ethnomathematics problem solving that can be practically implemented in mathematics classrooms.